Cultural and Health Management Practices of the Garo Community of Bangladesh: A Case Study of the Garos of Greater Mymensingh District - Sarker, Md Moklesur Rahman; Ghani, Abdul (Stamford Journal of Pharmaceutical Sciences, 2009)
An extensive survey study was carried out on different aspects of health management practices of the Garo communities in Bangladesh to assess their actual present health status. The study was carried out on 1205 respondents out of 40,173 total Garo people of the study area of greater Mymensingh district. The study revealed that Garos enjoy a better health status than the common Bengali community. It was also observed that traditional cultural practices have great influence on the health management of the Garos. Many of the Garos think that diseases result from the dissatisfaction of the gods and goddesses or curses of the evil spirits. Thus they sacrifice animals to please the spirits to get relief of their diseases. Almost all the Garos use water from tube well (53.69%) or puller pump (44.81%) for drinking, bathing and cleaning purposes. Every family has a latrine. Almost everybody is concerned about regular dental care and half of the Garos are concerned about family planning. Garos eat a wider variety of foods including numerous natural plants as vegetables, some of which have medicinal values. Traditionally Garos are fond of drinking wine, prepared from boiled rice. The study also revealed that the Garos are generally less attacked by diseases than the common Bengali people. This may be attributed to their better living environment, food habits, cleanliness, hard work in the fields and sufficient rest after work and, after all, consciousness about health and diseases. But yet, diseases are quite common in this community; the most common one being Malaria. Most of the Garos take treatment from their traditional health practitioners although treatment of modern Allopathic system is available in the local Christian hospitals. About 55.68% of the Garos expressed their firm faith on their traditional treatment systems. In spite of some superstitions about diseases and health, the overall health status of the Garos is comparatively better than the majority of the mainland Bengali community. Key Words: Garo community, Garo culture, Health management practices, Traditional healers doi:10.3329/sjps.v1i1.1783 S. J. Pharm. Sci. 1(1&2): 29-37